2011
DOI: 10.1111/j.1530-0277.2011.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Liver Function and Brain Shrinkage in Patients with Alcohol Dependence

Abstract: Background Oxidative stress has been proposed as one of the mechanisms of alcohol-induced brain shrinkage and alcohol-induced hepatotoxicity. The study aim was to assess the correlations between liver function and brain volume measurements in patients with alcohol dependence. Methods We recruited 124 patients with alcohol dependence and 111 healthy control subjects from National Institute of Health, National Institute on Alcohol Abuse and Alcoholism inpatient alcohol treatment program. Gamma glutamyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
4
20
0
1
Order By: Relevance
“…Previously, we found that magnetic resonance imaging measures of brain shrinkage in alcoholism were correlated with liver inflammation as quantified by serum GGT (Chen et al, 2012). The present study expands on this finding by demonstrating that the severity of liver inflammation is correlated with neuroinflammation as indexed by the concentration of MCP-1 in CSF.…”
Section: Discussionsupporting
confidence: 63%
“…Previously, we found that magnetic resonance imaging measures of brain shrinkage in alcoholism were correlated with liver inflammation as quantified by serum GGT (Chen et al, 2012). The present study expands on this finding by demonstrating that the severity of liver inflammation is correlated with neuroinflammation as indexed by the concentration of MCP-1 in CSF.…”
Section: Discussionsupporting
confidence: 63%
“…Smaller white matter volumes likewise have been reported (Harper et al, 1990; Pfefferbaum et al, 1995; Pfefferbaum et al, 2001b; Chen et al, 2012), including the corpus callosum (see Figure 1) (Pfefferbaum et al, 1996; Agartz et al, 1999; Ruiz et al, 2013). Smaller brain volume is accompanied by larger CSF volume (Pfefferbaum et al, 1992; Pfefferbaum et al, 1998; Agartz et al, 1999; Bendszus et al, 2001; Pfefferbaum et al, 2001b; Chen et al, 2012), and researchers have reported larger volumes of the lateral ventricles (Zipursky et al, 1989; Pfefferbaum et al, 1998; Pfefferbaum et al, 2001b; Ruiz et al, 2013) and the third ventricle (Pfefferbaum et al, 2001b). …”
Section: Profiles Of Damage and Repairmentioning
confidence: 53%
“…Relatively smaller volumes have been noted not only in total brain size (Pfefferbaum et al, 1992; Mann et al, 2005; Chen et al, 2012) including the cerebellum (Chanraud et al, 2007), but also in cerebral subdivisions and regional areas (Pfefferbaum et al, 1992; Pfefferbaum et al, 2001b; Makris et al, 2008; Fein et al, 2009; Chen et al, 2012) and numerous subcortical structures (Chanraud et al, 2007; Makris et al, 2008). Smaller white matter volumes likewise have been reported (Harper et al, 1990; Pfefferbaum et al, 1995; Pfefferbaum et al, 2001b; Chen et al, 2012), including the corpus callosum (see Figure 1) (Pfefferbaum et al, 1996; Agartz et al, 1999; Ruiz et al, 2013).…”
Section: Profiles Of Damage and Repairmentioning
confidence: 99%
See 2 more Smart Citations